The Influence of Leadership and Discipline on the Performance of Military Personnel at Satlinlamil Surabaya - Ariwibowo, Agung (Dinasti Publisher, 2025)
This study investigates the impact of leadership and discipline on the performance of military personnel at Satlinlamil Surabaya. Frequent rotations of department heads with differing leadership styles create transitional challenges that affect personnel performance. Additionally, a decline in discipline is observed among personnel nearing retirement and those living near their workplace, further affecting overall effectiveness. Using a mixed-methods approach that integrates quantitative surveys and qualitative interviews, the study examines how these factors influence operational outcomes. Key findings highlight the critical role of consistent leadership in fostering trust and productivity, as well as the importance of maintaining discipline to ensure organizational cohesion. Recommendations include structured leadership development programs, mentoring systems, and the integration of advanced performance monitoring tools to address these challenges. These findings contribute to a broader understanding of leadership and discipline dynamics in hierarchical organizations and offer practical solutions for enhancing military performance.